2008
DOI: 10.1021/np800435c
|View full text |Cite
|
Sign up to set email alerts
|

Jerantinines A−G, Cytotoxic Aspidosperma Alkaloids from Tabernaemontana corymbosa

Abstract: Seven new indole alkaloids of the Aspidosperma type, jerantinines A-G (1-7), were isolated from a leaf extract of the Malayan Tabernaemontana corymbosa. The structures were established using NMR and MS analysis. Five of the alkaloids isolated and two derivatives (1-5, 8, 9) displayed pronounced in vitro cytotoxicity against human KB cells (IC50 < 1 microg/mL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 30 publications
3
99
1
Order By: Relevance
“…22 After the encouraging results obtained in the case of aspidospermidine (30) and goniomitine (44), we decided to examine the synthesis of another indole alkaloid, jerantinine E (51). This compound had been isolated from the Malayan plant Tabernaemontana corymbosa by Kam and co-workers in 2008 and displayed interesting cytotoxicity, 23 but it had never been accessed synthetically. Using bis-methoxy indole derivative 45 instead of N-carboxy indole, the addition cyclization sequence worked also well to give tetracyclic intermediate 47.…”
Section: Cyclizations With Non-activated Aminocyclopropanesmentioning
confidence: 99%
“…22 After the encouraging results obtained in the case of aspidospermidine (30) and goniomitine (44), we decided to examine the synthesis of another indole alkaloid, jerantinine E (51). This compound had been isolated from the Malayan plant Tabernaemontana corymbosa by Kam and co-workers in 2008 and displayed interesting cytotoxicity, 23 but it had never been accessed synthetically. Using bis-methoxy indole derivative 45 instead of N-carboxy indole, the addition cyclization sequence worked also well to give tetracyclic intermediate 47.…”
Section: Cyclizations With Non-activated Aminocyclopropanesmentioning
confidence: 99%
“…The 1 H and 13 C NMR data of 1 are somewhat similar to those of tabersonine alkaloids, particularly jerantinines AÀE (Lim et al, 2008). However, the N(4)-C(3)-C(14)-C(15) fragment usually present in the tabersonine/Aspidosperma alkaloids was conspicuously absent in 1, being replaced instead by an N-acetyl and an isolated aldehyde group.…”
Section: Resultsmentioning
confidence: 65%
“…The same plant also yielded a number of new indole and bisindole alkaloids Kam andSim, 2003a,b, 2002a,b,c;Zhang et al, 2007;Zèches et al, 1994), including several vobasinyl-iboga bisindoles which reverse multidrug-resistance in vincristine resistant KB cells (Kam et al, 1998). In continuation of our studies of biologically active alkaloids from Malaysian Tabernaemontana (Kam et al, 2004a(Kam et al, ,b, 2003a(Kam et al, ,b, 2001(Kam et al, , 2000(Kam et al, , 1998(Kam et al, , 1992Kam and Sim, 2003a,b, 2002a,b,c, 2001, 1999, we recently reported the isolation of several new cytotoxic Aspidosperma-type alkaloids, jerantinines AÀG, from the leaf extract of the same species, but involving plant material collected from a different location (Lim et al, 2008). We now wish to report the further isolation of additional new alkaloids from the leaf extract of the same plant.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…So far, no other anticancer monoterpenoid indole alkaloids than vincristine analoges have been employed as drugs. Recently, it was reported that anticancer monomers of this type are as potent as the corresponding dimers (vincristine) [3]. The genus Alstonia of Apocynaceae is rich in monoterpenoid indole alkaloids.…”
mentioning
confidence: 99%